2019
DOI: 10.1093/mnras/stz1003
|View full text |Cite
|
Sign up to set email alerts
|

Torus model properties of an ultra-hard X-ray selected sample of Seyfert galaxies

Abstract: We characterize for the first time the torus properties of an ultra-hard X-ray (14-195 keV) volume-limited (D L <40 Mpc) sample of 24 Seyfert (Sy) galaxies (BCS 40 sample). The sample was selected from the Swift/BAT nine month catalog. We use high angular resolution nuclear infrared (IR) photometry and N-band spectroscopy, the CLUMPY torus models and a Bayesian tool to characterize the properties of the nuclear dust. In the case of the Sy1s we estimate the accretion disk contribution to the subarcsecond resolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 143 publications
(153 reference statements)
3
47
0
Order By: Relevance
“…Torus models also incorporated an additional polar dust component to account for the mid-IR imaging and interferometric observations of some Seyfert galaxies Gallagher et al 2015;Hönig & Kishimoto 2017;Stalevski et al 2017;Isbell et al 2021). These models reproduced satisfactorily the observed nuclear IR emission of samples of nearby AGN (see e.g., Ramos Almeida et al 2009Alonso-Herrero et al 2011;Ichikawa et al 2015;García-González et al 2017;García-Bernete et al 2019;González-Martín et al 2019). Elitzur & Shlosman (2006) put forward a scenario where the torus is part of a clumpy outflow, and recently Venanzi et al (2020) demonstrated theoretically that dusty winds can be launched at the inner walls of the torus.…”
Section: Introductionmentioning
confidence: 86%
“…Torus models also incorporated an additional polar dust component to account for the mid-IR imaging and interferometric observations of some Seyfert galaxies Gallagher et al 2015;Hönig & Kishimoto 2017;Stalevski et al 2017;Isbell et al 2021). These models reproduced satisfactorily the observed nuclear IR emission of samples of nearby AGN (see e.g., Ramos Almeida et al 2009Alonso-Herrero et al 2011;Ichikawa et al 2015;García-González et al 2017;García-Bernete et al 2019;González-Martín et al 2019). Elitzur & Shlosman (2006) put forward a scenario where the torus is part of a clumpy outflow, and recently Venanzi et al (2020) demonstrated theoretically that dusty winds can be launched at the inner walls of the torus.…”
Section: Introductionmentioning
confidence: 86%
“…However, as shown in this paper, when this contribution is large (stellar component contributing at least 50% compared to the torus component at 5 µm, or dust heated by star-formation contributing at least 50% compared to the torus component at 30 µm) dilution strongly influences the parameter determination. High spatial resolution observations are needed for the best isolation of the dust associated the AGN from other contributors, as those provided with ground-based facilities (Ramos Almeida et al 2009;Fuller et al 2016;Martínez-Paredes et al 2017;García-Bernete et al 2019), the novel combination of VLTI+GRAVITY and the future JWST. Note however that both N-and Q-bands groundbased spectra are available only for NGC 1068.…”
Section: Goodness Of Parameter Determinationmentioning
confidence: 99%
“…A large body of work using SED fits to local AGNs (e.g., Ramos Almeida et al 2009;Alonso-Herrero et al 2011;Lira et al 2013;García-González et al 2016;García-Bernete et al 2019;Martínez-Paredes et al 2020) suggests that L and M observations at high sensitivity and angular resolution are required to study the physical properties of the 3-5 μm radiation bump. In fact, Lira et al (2013) emphasized that spectral information at 5 μm is necessary to properly constrain their SED fits.…”
Section: Introductionmentioning
confidence: 99%